Post‐treatment urinary sarcosine as a predictor of recurrent relapses in patients with prostate cancer. (12th September 2018) - Gumulec, Jaromir; Raudenska, Martina; Pacik, Dalibor; Plevova, Mariana; Sorokac‐Kubolkova, Alena; Lackova, Zuzana; Cernei, Natalia; Strmiska, Vladislav; Zitka, Ondrej; Heger, Zbynek; Adam, Vojtech
Abstract: To date, there has been no evidence regarding the association between urinary sarcosine content and prostate cancer survival. Our main objective was to investigate whether levels of post‐treatment urinary sarcosine are associated with relapse. The inclusion criteria were (in accordance with EAU 2017) as follows: histopathologically verified adenocarcinoma in prostate biopsy cores or specimens from transurethral resection of the prostate (TURP) or prostatectomy for benign prostatic enlargement (BPE) with retained ability to urinate. The median follow‐up was 53 months. In the study, we retrospectively evaluated a cohort of 511 patients with prostate cancer with various risk factors and treatment strategies. Post‐treatment sarcosine levels were elevated in 266 (52%) patients and highly elevated (≥200 nmol/L) in 71 (13%) patients. Urinary sarcosine content was significantly associated with number of relapses that patients experienced, P  = 0.002 for sarcosine ≥200 vs ≤30 nmol/L. Multivariate analysis revealed that sarcosine was an independent predictor of recurrent relapses (≥2 relapses with an intermediate period of remission), HR = 3.89 (95% CI 1.29‐11.7) for sarcosine >200 vs <30 nmol/L. This trend was even more pronounced in a subgroup of patients who underwent radical prostatectomy, HR = 3.29 (95% CI 1.06‐10.18), where (single) relapse‐free survival could also be predicted by sarcosine levels, HR = 1.96 (1.05‐3.66). Urinary sarcosine may become a possible predictor for patients' outcomes, because patients with elevated post‐treatment sarcosine could be predicted to have recurrent relapses of the disease. Abstract : Risk of relapses is increased in prostate cancer patients with high post‐treatment urinary sarcosine, as shown by a retrospective study on 511 patients.